Características físico-químicas, compostos fenólicos capacidade antioxidante e atividade da polifenoloxidase durante a fermentação de cacau (Theobroma cacao L.) cultivado no Espírito Santo - Casotti, Bárbara Nicchio (2024)
Cocoa is considered one of the largest natural sources of phenolic compounds. There are a variety of positive health effects related to the consumption of these compounds described in the literature, such as high antioxidant, anti inflammatory, anticarcinogenic, antimicrobial, analgesic and vasodilatory capacity. Cocoa fermentation is the most important step in processing, where changes in the levels of several compounds, including phenolics, occur. Considering the influence of the fermentation process of these compounds on the antioxidant capacity and enzymatic activity, which influence the transformation of cocoa seeds during this process, the present study aimed to evaluate the levels of total phenolic compounds during fermentation at room conditions of two cocoa clones, PH16 and SJ02, produced in Espírito Santo, and the fermentation of clone PH16 with and without control of ambient temperature and humidity. Clones PH16 and SJ02 differed statistically (p < 0.05) only in the soluble solids content of the pulp. The fermentation of cocoa seeds under controlled conditions showed a decrease in the content of phenolic compounds during the process, while in the fermentation carried out under ambient conditions, constancy was observed, with significant differences between treatments for this parameter (p < 0.05). The temperature also showed significant differences (p < 0.05) over time, especially during the temperature under ambient conditions, where temperature fluctuations were more pronounced, evidencing the influence of the control of temperature conditions on these sessions